Visual Memes as Neutralizers of Political Dissent - Stefka Hristova (tripleC: Communication, Capitalism & Critique)
A meme, conceived as the cultural equivalent of the biological gene by Richard Dawkins, spread through culture like a virus – quickly and widely. Its viral power is in turn understood as product of nature, rather than culture – or rather as threatening to subvert culture into a condition of nature. Firing up over night, and disappearing just as quickly, memes are often allowed to run their course and fade into oblivion, only to return again.  They emerge at moments of contestation of dominant narratives and through their participatory structure of imitation and mutation allow for the dissolution of points of ideological conflict and the reestablishment of a normative narrative. If not too threatening to the health of the state body, these cultural viruses are left unchecked as they build the immunity, and further, in Derrida’s terms, the “autoimmunity” of the nation-state. In this project, I explore the role of visual Internet memes as neutralizers of contested past and present narratives of occupation and dissent by focusing the digital visual memes associated with the Occupy Movement in the United States. More specifically, I examine the emergence of the term “occupy” as an visual Internet meme in and of itself – Occupy Wall Street spurred Occupy Chicago, Oakland and even Sesame Street and the North Pole, as well as a marker of a revolution - revolving viral civil and political dissent. I argue that there is a notable distinction between physical participation the Occupy Movement and virtual participation through the reworking of Occupy’s memes, where as the first modality serves as an active disruptor of the political normative imaginary, the second works in precisely the opposite fashion  - in its reconstitution of a common-sense dominant image of the political.